2012
DOI: 10.1097/rlu.0b013e318248524a
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT and Diffusion-Weighted Imaging of Head and Neck Squamous Cell Carcinoma

Abstract: These results suggest that pretreatment primary tumor SUV(max) and ADC correlate significantly and negatively and both may have similar potential to predict DFS or disease events of HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 27 publications
5
31
0
Order By: Relevance
“…Recently, Rakheja et al found statistically significant inverse correlations between maximum SUVs and minimum ADC values and mean SUVs and mean ADC values in 69 [ 18 F] FDG avid malignant lesions derived from simultaneous FDG PET/MRI [17]. Nakajo et al report of significant inverse correlations of maximum SUVs derived from FDG PET/CT and ADC values in squamous cell carcinoma of the head and neck region [18]. However, there are also reports revealing that SUVs and ADC values do not inversely correlate significantly, as for example shown by Varoquaux et al in a study about head and neck squamous cell carcinoma [19].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rakheja et al found statistically significant inverse correlations between maximum SUVs and minimum ADC values and mean SUVs and mean ADC values in 69 [ 18 F] FDG avid malignant lesions derived from simultaneous FDG PET/MRI [17]. Nakajo et al report of significant inverse correlations of maximum SUVs derived from FDG PET/CT and ADC values in squamous cell carcinoma of the head and neck region [18]. However, there are also reports revealing that SUVs and ADC values do not inversely correlate significantly, as for example shown by Varoquaux et al in a study about head and neck squamous cell carcinoma [19].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated for head and neck cancers that SUVmax is inversely correlated to ADC ratio between different b-values [39] or ADC ratio between minimum and mean [40]. However, Nakajo and co-authors have shown a negative and significant correlation between SUVmax and ADC mean, studying 26 patients with HNSCC before treatment [41]. Our results are probably different due to the fact that our population is heterogenous (as it is in any clinical routine), including different histologic types of HNC and not only primary tumors.…”
Section: Pet Values and Dwi Parametersmentioning
confidence: 91%
“…Recently there have been few reports showing correlations between these multimodality imaging techniques and their initial role in the prognosis of HNSCC patients[15]. However, there are limited studies initiated to explore the use of these techniques together in a treatment planning setting for radiation oncology[16].…”
Section: Introductionmentioning
confidence: 99%